Generazioni di attori. Il carteggio di Adelaide con Maddalena Ristori e gli affanni della capocomica - Simoncini, Francesca (Drammaturgia, 2023)
This essay aims to submit a first survey of the substantial correspondence between Antonio and Maddalena Ristori, both actors, with their daughter Adelaide. The letters, preserved in the Museo Biblioteca dell’Attore in Genoa, allow us to reconstruct the private narrative of the great artist who tells about her travel adventures, her artistic and economic successes and her troubles as a woman, an actress and a capocomica. Her parents’ craft knowledge and ‘art’ relationships allow the actress to have information on actors and actresses to be hired in the company and updates on the performances’ trends staged in Florence where they live. The sequential consultation of the manuscripts finds out the Great Actress at the centre of a generational transmission of the craft and highlights the transformations that she introduced into the tradition. The correspondence, currently in the course of complete transcription, will be the subject of a forthcoming publication.